Peningkatan Kapasitas dan Daya Saing UMKM Melalui Seminar Pemberdayaan - Karima, Kuni Nabila; Faizah, Fita Nurotul; Abdillah, Muhammad Riziq Iksan (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
This service aims to increase the capacity of MSME players through training in business management, product marketing and the use of technology. The method used is PAR (Participatory Action Research) by holding interactive workshops and direct guidance. This activity was carried out in July 2024 involving 30 participants from various MSME sectors in Warungasem Village, Batang. The results of this service show that participants experienced a significant increase in their understanding of business management, marketing strategies, and were more confident in adopting new technology. This can be seen from the use of technology as a marketing model, namely social media. On the other hand, positive impacts can be seen from increasing income, market reach of MSMEs, as well as strengthening networks between business actors, government and local communities, which supports the sustainability and growth of MSMEs in the future.